2002
DOI: 10.1139/g01-140
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite marker analysis of an anther-derived potato family: skewed segregation and gene–centromere mapping

Abstract: Segregation patterns of polymorphic simple sequence repeat (SSR) primer pairs were investigated in monoploid potato families derived from anther culture. A total of 14 primers developed from the sequences in the database, as well as from a genomic library of potato, was used. Distorted segregation was observed for seven (50%) polymorphic loci among monoploids derived from an interspecific hybrid. Similar distortion was observed for only one of five loci that could be contrasted between the two monoploid famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
(40 reference statements)
2
12
0
Order By: Relevance
“…This high level of segregation distortion was also observed with RFLPs in the same mapping population and has possibly been caused during the development of the doubledhaploids (Graner et al 1991). Deviations from the expected Mendelian segregation ratios were previously reported for mapping in many different plants based on both co-dominant and dominant marker types (Lyttle 1991;Xu et al 1997;Chani et al 2002;Knox and Ellis 2002). In a study of SSR mapping in maize (Sharopova et al 2002), no evidence was found that the order of markers was influenced by distorted segregation.…”
Section: Mapping Of Microsatellite Locisupporting
confidence: 76%
“…This high level of segregation distortion was also observed with RFLPs in the same mapping population and has possibly been caused during the development of the doubledhaploids (Graner et al 1991). Deviations from the expected Mendelian segregation ratios were previously reported for mapping in many different plants based on both co-dominant and dominant marker types (Lyttle 1991;Xu et al 1997;Chani et al 2002;Knox and Ellis 2002). In a study of SSR mapping in maize (Sharopova et al 2002), no evidence was found that the order of markers was influenced by distorted segregation.…”
Section: Mapping Of Microsatellite Locisupporting
confidence: 76%
“…The first was the localization of centromeres on 12 potato chromosomes and the second was the proof of a single crossover per chromosome arm. Previously these two issues for potato chromosome were reported in a few articles (Mendiburu and Peloquin 1979;Douches and Quiros 1987;Bastiaanssen et al 1996;Bastiaanssen 1997;Chani et al 2002). However, they were theoretically proposed or the numbers of loci or chromosomes were limited.…”
Section: Discussionmentioning
confidence: 99%
“…Since both the androgenic (di)haploids represent the gametes directly and SSR is a codominant marker, it is possible to explain the reasons for such high polymorphism based on recombination vis-à-vis crossover events. The microsatellite locus POTM1-2 representing a dinucleotide repeat (AT) has been mapped at the farthest (42.65 cM) from the centromere (Chani et al 2002) amongst the other loci characterized in this study, for which gene-centromere map positions are available. This provides a strong basis for high polymorphism detected at this locus because the probability of a crossover in meiosis increases with distance from the centromere (Chani et al 2000), accepting the hypothesis of a single crossover per chromosome arm in potato microspores (Bastiaanssen et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the androgenic competence of tetraploid potatoes was also assessed, and the anther-derived plants obtained were characterized for ploidy level, chromosome number and nuclear DNA variation. DNA markers have been extensively used for assessing the genetic variation and for determining the genetic composition of anther-derived plants in potato (Birhman et al 1994;Rivard et al 1994;Veilleux et al 1995;Chani et al 2000Chani et al , 2002. All these studies were, however, confined to the genetic analyses of monoploid and/or diploid anther-derived plants, which originated from diploid S. chacoense or S. phureja anther donors, or their interspecific hybrids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation